Comparative Study of Antioxidant Phycocyanin Extracts Activity between S. platensis with S. fusiformis Using DPPH Method - Dwi Margiati; Danni Ramdani; Asri Peni Wulandari (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Phycocyanin is Spirulina’s content which has antioxidant activity to inhibit oxidation process or formation of free radicals that play a role in the initiation high-degenerative diseases. This research is aim to determine the best antioxidant activity of S. platensis with S. fusiformis through the best extraction methods of Spirulina cell between distilled water and PBS (Phosphate Buffer Solution). This research method existed Spirulina cell extraction used distilled water and PBS, and then followed by fractionation and dialysis phycocyanin extract, afterward tested the antioxidant activity used DPPH method. The result of extraction used PBS with a salt concentration of ammonium sulfate 30% produced the best purity value of phycocyanin extract of both types of Spirulina. Results of tested the antioxidant activity, S. fusiformis has the best antioxidant activity compared with S .platensis with a value of 311.43 ppm and 387.36 ppm, respectively.Keywords: Antioxidant, DPPH, Phycocyanin extracts, S. fusiformis, S. Platensis